(untitled) (LACCEI, 2024)
microstructure, susceptibility to cold cracking, hardness, and HAZ extension in the joint of AISI 9260 steel plates welded by SMAW process with E7018 filler electrode has been studied. A one-factor design with 5 levels of the variable (100°C, 140 °C, 180°C, 220°C, and 260°C), three experiment replicates, and three process control tests was used, resulting in 18 total tests. Each specimen, according to WIC standard, consists of two AISI 9260 steel plates of 50.0 x 76.0 x 12.5 mm, joined in a "V" shape with a root separation of 1.0 mm, mounted on a cooling plate made of A36 steel with dimensions of 70.0 x 180.0 x 12.5 mm. The initial temperature before preheating was 9°C. The welding was performed according to a randomized test design, executing 3 multi-pass welds and controlled start and interpass preheating before placing on an aluminum rail at 14°C. The hardness profiles versus microstructure at 4 selected points (ZF, HAZ, HAZ final line, and MB) show the relationship between hardness and microstructural changes due to preheating temperatures, process energy, and filler material. Microcracks were observed in the HAZ of almost all specimens. In the HAZ, new microconstituents generated zones of extreme hardness under the weld bead and low hardness zones due to overtempering. The measured distances from the center of the weld bead to these zones and to the maximum HAZ end increased as preheating temperature increased from 9°C to 260°C for SMAW. In the ZF, columnar zones and refined zones with typical microconstituents were observed, and the resulting hardness values were low, with minimum hardness values of 182 Hv5.0 and 186 Hv5.0 after using the SMAW process and remained approximately constant. The hardness levels in ZF for SMAW were not at an acceptable level for the welded joint service. An optimal preheating temperature in the temperature range studied for the given study conditions has not been determined. At temperatures above 426°C, there may be risks of overtempering, and the AISI 9260 steel would rapidly lose toughness. The elasticity conditions of the joint in HAZ and ZF for SMAW process due to the cooling rail at 14°C were affected compared to the base metal in the supply state, rendering the structure unusable for service